Religious and Cultural Existences Within the Communities of Upper Kapuas Riverside of West Kalimantan - Zaenuddin Hudi Prasojo (Graduate Program of Pontianak Institute of Islamic Studies, 2017)
The sudies on the issues related to communities in the interior of West Kalimantan begin to take place when Dutch and other European scholars in the colonial period came to the region. But they have been limitedly documented. The amount of research by local and foreign scholars in the region is still not significant when compared to that of research in Sarawak, Sabah and Brunei which are also situated on the island of Borneo. In fact, the natural wealth, cultural heritage and the rural communities of West Kalimantan need serious attention and studies for the purpose of the development of the region. In addition, local elements such as human and cutural resources may become potential supports of development to improve the welfare of the communities. This study highlights the significant contribution of religious and cultural aspects within the communities living around the upper Kapuas riverside. Acculturation of local and Islamic cultures have occurred since the advent of Islam into the interior areas of Kalimantan through the Kapuas River. The acculturation of local religions and cultures also promotes a very important local religious institution in the process of social change of the communities of the Kapuas riverside in the interior of West Kalimantan. The local religious institutions serve as an infrastructure that has been proven to ensure the survival of the living Muslim community system that existed among indigenous people who were still in the local beliefs of their time. This study also finds that the Muslim communities of the Kapuas Riverside in the interior of West Kalimantan already have extensive networks, not just the kinship network, Islamic trade and da'wah but also the network of scholarship. Of course, the growth of these growing networks is influenced by the media that also develops in its name. Thus this work also describes a comprehensive analysis of cultural and religious aspects in the development of communities of the Kapuas riverside in the interior of West Kalimantan which is currently included in the administrative areas of Sintang and Kapuas Hulu Districts.